Communicology and Culturology: Semiotic Phenomenological Method in Applied Small Group Research - Lanigan, Richard L. (Public Journal of Semiotics, 2013)
Communicology is the science of human communication where consciousness is constituted as a medium of communication at four interconnected levels of interaction experience: intrapersonal (embodied), interpersonal (dyadic), group (social), and inter-group (cultural). The focus of the paper is the group level of communication across generations, thus constituting inter-group communication that stabilizes norms (forms a culture). I propose to explicate the way in which the method of semiotic phenomenology informs the pioneering work at the University of Toronto by Tom McFeat, a Harvard trained cultural anthropologist, on small group cultures as an experimental research methodology. Rather than the cognitiveanalytic (Husserl‘s transcendental eidetic) techniques suggest by Don Ihde as a pseudo "experimental phenomenology", McFeat provides an applied method for the empirical experimental constitution of culture in conscious experience. Group cultures are constructed in the communicological practices of group formation and transformation by means of a selfgenerating group narrative (myth) design. McFeat‘s method consists of three steps of culture formation by communication that are: (1) Content-Ordering, (2) Task-Ordering, and (3) Group-Ordering, i.e., what Ernst Cassirer and Karl Jaspers call the logic of culture or Culturology. These steps are compared to the descriptive phenomenology research procedures suggested by Amedeo Giorgi following Husserl‘s approach: (1) Find a sense of the whole, (2) Determine meaning units, (3) Transform the natural attitude expressions into phenomenologically, psychologically sensitive expressions. A second correlation will be made to Richard Lanigan‘s semiotic phenomenology method following the work of Cassirer, Jaspers, and Merleau-Ponty: (1) Description of Signs, (2) Reduction of Signifiers, and (3) Interpretation of Signifieds.